IDH1 inhibitor-induced neutrophilic dermatosis in a patient with acute myeloid leukemia. (2022) - Dunn-Valadez, Sydney; Bathini, Srilakshmi; Elston, Carly; Rangaraju, Sravanti; Stasi, Antonio Di; Worth, Sarah; Morlote, Diana; Harada, Shuko; Vachhani, Pankit
Abstract: Ivosidenib is an oral inhibitor of mutant Isocitrate dehydrogenase 1 (IDH1). It is approved for treatment of patients with relapsed or refractory IDH1 -mutated acute myeloid leukemia (AML) and patients with newly diagnosed IDH1 -mutated AML who are 75 years or older or those who are ineligible to receive intensive chemotherapy. While generally well tolerated, differentiation syndrome has been reported in 15–20% of patients. Here, we report a case of acute febrile neutrophilic dermatosis or Sweet's syndrome in conjunction with the use of ivosidenib for the treatment of relapsed AML. We discuss the clinical presentation of this rare entity, review relevant literature, and comment on its association with differentiation syndrome.